West African cattle share non-random heterozygosity-rich region islands enriched on adaptation-related genes despite their different origins - Arias, Katherine D.; Fernández, Iván; Traoré, Amadou; Goyache, Félix (Frontiers in Animal Science, 2024)
MethodsUp to 237 individuals belonging to 10 different taurine (Bos taurus), zebu (B. indicus), and taurine × zebu sanga cattle populations sampled in Benin, Burkina Faso, and Niger were typed using the BovineHD BeadChip of Illumina to ascertain the patterns and importance of heterozygosity-rich regions (HRRs) in West African cattle. To account for among-population gene flow, individuals were further classified into three groups (Qtaurine, Qzebu, and admixed) according to maximum likelihood estimates of individual ancestries (q^) obtained using the program Admixture v1.23.Results and discussionThe 967 HRRs identified on 27 out of 29 bovine chromosomes in 231 cattle individuals were further summarized into 103 HRR islands, covering 40.7 Mb of the bovine genome. Only HRR islands identified in at least 10% of the animals typed or 10% of the individuals classified according to cattle type or admixture class were considered relevant to characterize the West African cattle genomic background. Only one and three HRR islands were considered taurine- and zebu-specific, respectively. Most (14) relevant HRR islands identified were present in cattle individuals despite the cattle type or admixture class into which they were classified (waHRR), suggesting that HRR can give advantages for adaptation to harsh environments. A total of 202 potential candidate genes were identified on the 14 waHRR islands. Most of them belonged to gene families coding zinc finger, protocadherin, adhesion G protein-coupled receptors, solute carrier, and arachidonate lipoxygenase proteins, involved in immune response, with a putative role in adaptation. Furthermore, waHRRs were also enriched on 18 and 11 different genes coding olfactory receptors and pregnancy-associated glycoproteins, respectively, giving additional support to the suggested importance of the HRR islands identified for the adaptive ability of West African cattle. Our research identified new genomic areas that can be targeted for further research in cattle adaptive ability.